Electron microscopic study of natural killer cell-tumor cell conjugates - Frey, Tom (1982)
Natural killer (NK) cells were obtained from C3H mouse spleens according to a modified version of the method of Kuribayashi et al. [Kuribayashi, K., Gillis, S., Dern, D. E. & Henney, C. S. (1981) J. Immunol. 126, 2321-2327]. These cells retain in vitro cytotoxicity against certain model tumor cell targets and appear homogeneous by morphological criteria. NK cells, YAC (tumor) cells, and NK cell-YAC cell conjugates have been examined with scanning (SEM) and transmission (TEM) electron microscopy. SEM experiments have shown that: (i) NK cells are large and possess various shapes in contrast to the YAC target cells which are smaller and round, (ii) YAC cells have uniformly distributed microvilli whereas the NK cell microvilli are most prominent in the area of effector-to-target contact, and (iii) in the absence of target cells, NK cell microvilli are found in a small number (usually 1-3) of cell surface locations. The region of NK cell-tumor cell contact has also been examined with TEM. The cells were stained with ruthenium red/OsO(4). The electron-dense ruthenium red/OsO(4) reaction product was consistently found in regions of close cell-cell contact, suggesting that carbohydrates were not completely cleared from areas of contact and that target and effector membranes do not fuse extensively. TEM observations indicate that NK cells have structurally unique granules. The granules are composed of at least two distinct compartments. The outer compartment contains the lysosome-associated enzymes acid phosphatase and inorganic trimetaphosphatase. No enzymatic activities have been found associated with the inner compartment. NK cells appear to degranulate when incubated with YAC cells. Under those circumstances, limited areas of the NK cytoplasm contain vacuole-like areas possessing granules and apparent granular debris. Degranulation appears to be involved in the cytotoxic function of NK cells.